A new damage-coupled cyclic plastic model for whole-life ratchetting of heat-treated U75V steel. (September 2020) - Wang, Ziyi; Xu, Xiang; Ding, Li; Kang, Guozheng; Wang, Ping; Kan, Qianhua
In the framework of continuum damage mechanics, a new damage-coupled cyclic plastic model is proposed to describe the nonlinear evolution of whole-life ratchetting and its dependence on the stress level. The characteristic that the damage evolution rate of U75V heat-treated steel decays in the initial load cycles is considered by introducing a modified term into classic damage evolution equation. A hybrid fatigue failure criterion considering both the fatigue and ratchetting strain-induced failures is established based on the fatigue failure rule concluded from experiments. Comparisons between simulated and experimental stress–strain hysteresis loops, ratchetting strains, damage evolutions, and fatigue lives are performed to validate the proposed model.